An examination of leader-member dyadic politeness of exchange and servant leadership on group member performance - Abu Bakar, Hassan; McCann, Robert M. (SAGE, 2018)
Integrating conversational constraint theory and models of homophily and relational dyadic communication, this study investigates how leader-member politeness exchange and servant leadership influence group member performance in a Malaysian organizational context. Using hierarchical linear modeling with data obtained from a sample of 510 employees, 65 workgroups, and 3 organizations, a politeness of exchange-servant leadership model was tested. Results show that servant leadership was positively and significantly associated with workgroup manager’s ratings of group member’s performance. The positive association between servant leadership and group member performance is more pronounced when managers and members in workgroups are high in politeness of exchange in their interactions. As predicted, leader-member dyadic politeness of exchange within the workgroup manager-group member dyads moderated this positive association.